2018
DOI: 10.1111/echo.13883
|View full text |Cite
|
Sign up to set email alerts
|

A rare giant congenital left atrial appendage aneurysm in a 1‐day‐old newborn

Abstract: Congenital left atrial appendage aneurysm (LAAA) is a very rare condition and occurs as a result of congenital dysplasia of musculi pectinate. These patients may be asymptomatic and/or may present with dyspnea, and thromboembolic events. The most common complications are life-threatening thromboembolic events and supraventricular tachyarrhythmias. Transthoracic echocardiography plays a very important role in the diagnosis of LAAA. Herein, we present a rare case of giant congenital LAAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
1
1
Order By: Relevance
“…Although asymptomatic patients are sporadically diagnosed during adulthood, 1 there are no reports of rapid left atrial appendage aneurysm enlargement and symptomatic features in the neonatal period, or of cardiac failure symptoms associated with left atrial appendage aneurysm expansion. Previous surgical cases in neonates have reported left atrial appendage aneurysm sizes of approximately 30 mm [2][3][4] , while the aneurysm in the present case was nearly twice as large. With rapid left atrial appendage aneurysm enlargement, the circulatory blood volume decreased and the main pulmonary artery was compressed.…”
Section: Discussioncontrasting
confidence: 46%
“…Although asymptomatic patients are sporadically diagnosed during adulthood, 1 there are no reports of rapid left atrial appendage aneurysm enlargement and symptomatic features in the neonatal period, or of cardiac failure symptoms associated with left atrial appendage aneurysm expansion. Previous surgical cases in neonates have reported left atrial appendage aneurysm sizes of approximately 30 mm [2][3][4] , while the aneurysm in the present case was nearly twice as large. With rapid left atrial appendage aneurysm enlargement, the circulatory blood volume decreased and the main pulmonary artery was compressed.…”
Section: Discussioncontrasting
confidence: 46%
“…An aneurysm within the left atrial appendage (LAAA) is a rare congenital anomaly that has been described in the literature, particularly in infants. Although their causes are unknown, in one case it has been reported to be associated with a focal aplasia of the pericardium* 1 . Thromboembolism, atrial arrhythmias and congestive heart failure have been reported as complications; however, the natural history is not well known.…”
Section: Introductionmentioning
confidence: 99%